ARTIFICIAL INTELLIGENCE AND TEACHING FOREIGN LANGUAGES FOR STUDENTS - Khayrullayeva Dilorom Sayfutdinovna (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This paper explores the evolving role of Artificial Intelligence (AI) in foreign language education within university settings. Drawing from recent empirical studies and institutional case analyses, it examines how AI technologies enhance personalization, support skill development, and promote learner autonomy. The study highlights practical applications such as speech recognition, adaptive learning systems, and intelligent tutoring, while addressing critical issues including algorithmic bias, digital inequity, and the need for pedagogical alignment. The analysis suggests that while AI holds significant potential to improve language learning outcomes, its successful integration depends on ethical design, institutional support, and the continued involvement of educators. The paper concludes with recommendations for future research and implementation strategies aimed at maximizing the pedagogical benefits of AI while mitigating its limitations.